Redox-catalysis flow electrode desalination in an organic solvent. Issue 39 (29th September 2021) - Wei, Qiang; Tang, Lufan; Ramalingam, Karthick; Liang, Mengjun; Ma, Jinxing; Shi, Yumeng; Hui, Kwun Nam; Hui, Kwan San; Chen, Fuming
Abstract : An organic redox flow electrode in FCDI is proposed to achieve quick salt removal and low energy consumption. The energy consumption is zero using a photoanode as the driving force. Abstract : The typical flow electrode capacitive deionization (FCDI) device uses carbon materials as flow electrodes in aqueous conditions. The low salt removal rate and high energy consumption have hindered further development. In this study, we propose an organic redox flow electrode in FCDI to achieve a quick salt removal process and low energy consumption. The organic medium, i.e., acetonitrile, containing 50 mM NaI/30 mM I2 electrolyte as the redox couples replaces the conventional water-based electrolyte. With the addition of 3 wt% multi-wall carbon nanotubes with the –NH2 group, the highest desalination rate of 6.8 μg cm −2 s −1 could be achieved at a current density of 13 mA cm −2, which is the highest desalination rate in capacitive deionization systems applied to date. Furthermore, the electrical energy consumption is reduced to zero when using the light illumination on the semiconductor as the driving force. The high-performance FCDI device based on the organic redox electrodes is of great significance for the practical desalination application at a low energy cost.